Pemahaman warna pada siswa kelas 1–2 SD melalui kegiatan mewarnai sebagai stimulus kreativitas di lembaga kursus - Elisia, Milarosa; Sumarwahyudi, Sumarwahyudi (Universitas Negeri Malang, 2026)
This study is based on variations in color understanding among first- and second-grade elementary students during coloring activities at LKP Windyas Club Malang. These differences influence the development of children’s visual creativity. Drawing on Johannes Itten’s color theory and J. P. Guilford’s concept of creativity, this research aims to examine the relationship between color understanding and creative ability in non-formal art learning. A descriptive qualitative approach was employed, with data collected through observation, interviews, and documentation. Data analysis followed the Miles and Huberman model, including data reduction, data display, and conclusion drawing, supported by triangulation to ensure validity. The findings reveal that most children show improvement in color understanding, indicated by their ability to select, combine, and apply colors appropriately, along with better neatness and stroke control. Coloring activities stimulate creativity by allowing children to explore color variations and add visual details. Supporting factors include children’s interest, a conducive learning environment, and instructor guidance, while inhibiting factors involve limited focus, fine motor skill constraints, and emotional conditions. Overall, coloring activities play a significant role in enhancing both color comprehension and children’s creativity.